Choosing to lead understanding Congressional foreign policy entrepreneurs - Carter, Ralph G. (Duke University Press, 2009)
Beyond the White House : bringing Congress into the foreign policy picture -- From problem to policy : a theory of Congressional foreign policy entrepreneurship -- Surveying the landscape : Congressional foreign policy entrepreneurs since World War II -- The rising tide : entrepreneurship in the Cold War consensus period, 1946/1967 -- Players in the game : entrepreneurship in the cold war dissensus period, 1968/1989 -- Contending with the thaw : entrepreneurship in the post/Cold War period, 1990/2000 -- After 9/11 : entrepreneurs into the 21st century -- Part of the landscape : conclusions on the entrepreneur effect